Feeding practices of selected Filipino caregivers of school-age children in Marikina private schools - Posadas, Maria Francesca B.; Tesea, Lyka Francesca B.; Torres, Larren Kyle D.; Aquino, maria Fema S. (Quezon City University of the Philippines Diliman, 2023)
School-age children (5–10 years old) are at risk for malnutrition due to their heightened nutrient requirements. Hence, schoolchildren must develop healthy eating habits, which their caregivers’ feeding practices can influence. The primary objective of the study was to describe the feeding practices and experiences of selected Filipino caregivers from Marikina City with their school-age children from private schools using a mixed-methods study design. Specifically, the study aimed to determine the feeding practices of caregivers based on the 12 dimensions of the Comprehensive Feeding Practices Questionnaire (CFPQ) and their challenges and strategies in child feeding. Through simple random sampling, fifty-five (55) participants were chosen to answer a survey followed by an interview. Descriptive statistics and thematic analysis were used to analyze the data. Results showed that modeling and child control were the most and least used feeding practices, respectively. Challenges in feeding that were identified include (1) picky eating, (2) consumption of less healthy foods, (3) slow eating and undereating, and (4) use of gadgets during meals. Meanwhile, the strategies were (1) verbal methods; (2) feeding independence; (3) reward system; (4) food preparation techniques; and (5) spoon-feeding. The findings of this study will help caregivers of school-age children about the feeding practices and strategies they may use to overcome challenges in feeding. Moreover, the study may serve as a basis for nutrition programs and interventions for Filipino caregivers and children in schools and communities.
Thesis
Includes bibliographical references (pages 127- 156)
Keywords: School children -- Philippines -- Marikina City -- Nutrition; School children -- Philippines -- Marikina City -- Food; Caregivers -- Philippines -- Maikina City